2011
DOI: 10.1002/erv.1154
|View full text |Cite
|
Sign up to set email alerts
|

Poor Decision Making in Male Patients with Anorexia Nervosa

Abstract: Impaired decision making is present in male and female patients with AN. These data suggest that male patients with AN are very similar to female patients in decision making, and as a result, treatment approaches that seek to improve this ability should be similar in both genders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
1
5

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 18 publications
4
29
1
5
Order By: Relevance
“…Group differences were more marked on the cognitive flexibility and decision making domains, although the inhibition response task also showed marginally statistical differences. Therefore, cognitive results are in agreement with several previous neuropsychological studies showing that EWC deficits extend to several executive processes [32], [33], [36], [37], [39][41], [44], [55], [56], almost certainly relying on the functioning of different fronto striatal systems, including the dorsolateral prefrontal cortex and the orbitofrontal cortex [21], [57][59].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Group differences were more marked on the cognitive flexibility and decision making domains, although the inhibition response task also showed marginally statistical differences. Therefore, cognitive results are in agreement with several previous neuropsychological studies showing that EWC deficits extend to several executive processes [32], [33], [36], [37], [39][41], [44], [55], [56], almost certainly relying on the functioning of different fronto striatal systems, including the dorsolateral prefrontal cortex and the orbitofrontal cortex [21], [57][59].…”
Section: Discussionsupporting
confidence: 91%
“…Both, AN and OB subjects go for choices that result in elevated immediate gains despite important future losses, showing a similar level of impairment between them. Therefore, according to previous general conducted studies [32], [39], [40], [42][44], [55], [56], the extreme eating/weight behaviors of these subjects might partially be an expression of their incapacity to successfully regulate reward and punishment, which might be translated into deficit in planning every day functioning. From a clinical perspective, it might be postulated that there are reasonable similarities between their test performance and their day to day pathological eating behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eating disorders share neuropsychiatric co-morbidity and certain susceptibility genes with mood disorder, impulsiveness and substance abuse [155,156] with greater suicide prevalence among anorexia nervosa patients [157]. Tchanturia et al [158] have found impaired decision-making in both male and female patients presenting eating disorder. Concurrently, it was shown that internalizing problems (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with AN have been shown to possess poor decisionmaking abilities (Tchanturia et al 2012) and are inclined to logically and rationally defend their food choices. Cognitive distortions are often difficult to correct, and in P.'s case there was limited success with CBT.…”
Section: Paul Mehta and Coffeymentioning
confidence: 99%